IMPLEMENTATION OF DIGITAL MARKETING THROUGH INTEGRATED FACEBOOK AND INSTAGRAM ADVERTISING PLATFORMS TO INCREASE CUSTOMER ACQUISITION (CASE STUDY: FATHIR THERAPY HOLISTIC CARE CLINIC MAKASSAR) - Nurul Aulia Mentari; Syamsu Alam; Muh. Jamil (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2025)
This study aims to implement and analyze the effectiveness of digital marketing through an integrated platform comprising Facebook Ads, Instagram Ads, and a website in increasing the number of customers at Fathir Therapy Holistic Care Makassar. The research method employed is Research and Development (R&D) using the Four-D (4D) model, which consists of four stages: define, design, develop, and disseminate. The define stage identifies the clinic's needs, including the suboptimal use of digital media. In the design stage, visual content and advertising strategies are developed using Canva and CapCut to support social media campaigns. A WordPress-based website is also created as an information hub and integration platform. The develop stage involves testing the digital marketing strategies, while the disseminate stage includes campaign implementation and result analysis. The findings reveal that the application of integrated platform-based digital marketing significantly increases customer reach and engagement. The effectiveness ratio shows a customer growth rate that exceeds the predetermined target. This implementation also offers a strategic solution to enhance business visibility in the digital era while strengthening Fathir Therapy Holistic Care's reputation as a trusted healthcare service provider.